Analysis and Simulation on Torque Ripples of Brushless DC Motor - Qian Weikang; Shi Yutao (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Because of its small size, high reliability, efficiency, and its output torque characteristics, brushless DC motor (BLDCM) had been widely used in many field of robotics, precision instruments and equipment, etc. However, its inherent electromagnetic torque ripple limited the scope of its application, which was the focus and difficulty of its research in recent years. This article first described the causes of brushless DC motor torque ripple, and then torque ripple generated by four PWM modulations was analyzed to get optimum control scheme, finally the MATLAB / SIMULINK simulation model verified the analysis of the results. This paper provided the most intuitionistic exhibition.